The Tissue Distribution of Lutein in Laying Hens Fed Lutein Fortified Chlorella and Production of Chicken Eggs Enriched with Lutein - An, Byoung-Ki (Korean J Food Sci Anim Resour, 2014)
Two experiments were conducted to investigate the dietary effects of conventional or lutein fortified chlorella on lutein absorptions, the tissue distributions and the changes in lutein content of eggs in laying hens. In Exp 1, a total of one hundred and fifty, 70 wk-old Hy-Line brown layers were divided into three groups with five replicates and fed with each experiment diet (control diet, diet with 1% conventional chlorella or lutein fortified chlorella) for 2 wk, respectively. The egg production in groups fed diets containing both chlorella powders were higher than that of the control group (p<0.01). With chlorella supplementations, the yolk color significantly increased, although there were no significant differences in the eggshell qualities. The lutein contents of serum, liver and growing oocytes were greatly increased by feeding conventional or lutein fortified chlorella (p<0.01). In Exp. 2, a total of ninety 60 wk-old Hy-Line brown layers were assigned into three groups with three replicates per group (10 birds per replicate). The birds were fed with one of three experimental diets (0, 0.1 or 0.2% lutein fortified chlorella) for 2 wk, respectively. The egg production was not affected by dietary treatments. The egg weight in the group fed with diet containing 0.2% of lutein fortified chlorella was higher than that of the control (p<0.05). As the dietary chlorella levels increased, the daily egg mass linearly increased, although not significantly. The yolk colors in groups fed diets containing lutein fortified chlorella were dramatically increased as compared to the control (p<0.001). The lutein in chicken eggs significantly increased when fed with 0.2% of lutein fortified chlorella (p<0.01). These results suggested that the dietary lutein derived from chlorella was readily absorbed into the serum and absorbed by the liver with growing oocyte for commercial laying hens. Particularly, the lutein fortified chlorella was a valuable natural source for the production of lutein enriched chicken eggs.